On the Marcinkiewicz–Zygmund law of large numbers in Banach lattices - Matsak, I. K.; Plichko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We strengthen the well-known Marcinkiewicz–Zygmund law of large numbers in the case of Banach lattices. Examples of applications to empirical distributions are presented.